Holocene palaeoclimatic evolution in the North Ionian Basin of the Mediterranean Sea: A multiproxy approach - L. Bronzo; A. Cascella; S. Bonomo; C. Morigi; I. Cacho; G. Margaritelli; J. Frigola; L.D. Pena; F. Lirer (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

New insights into the climate of northern Iberia during the Younger Dryas and Holocene: The Mendukilo multi-speleothem record - J.L. Bernal-Wormull; A. Moreno; M. Bartolomé; M. Arriolabengoa; C. Pérez-Mejías; E. Iriarte; C. Osácar; C. Spötl; H. Stoll; I. Cacho; R.L. Edwards; H. Cheng (Quaternary Science Reviews, 2023)

Economic, social, and environmental assessment of farming Nile tilapia in net-cages in a reservoir in hot semi-arid region during an extended drought event - Gustavo Gonzaga Henry-Silva; Júlio César da Silva Cacho; Rodrigo Sávio Teixeira Moura; Dallas Lee Flickinger; Wagner C. Valenti (Environmental Science and Pollution Research, 2022)

Epidemiology of Non-Tuberculous Mycobacteria isolated from clinical specimens in Madrid, Spain, from 2013 to 2017 - P López-Roa; E Aznar; J Cacho; R Cogollos-Agruña; D Domingo; MI García-Arata; R Millán; M Páez; E Perez-Cecilia; MJ Ruiz-Serrano; M Simón; M Tato; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Recurrent Magdalenian occupation in the interior of the Iberian Peninsula: new insights from the archaeological site of La Peña de Estebanvela (Segovia, Spain) - J. Yravedra; M. Andrés-Chaín; C. Cacho; J. A. Martos; L. Marquer; B. Avezuela; J. Jordá-Pardo; I. Martín-Lerma; C. Sesé; J. Valdivia (Archaeological and Anthropological Sciences, 2019)

The power and pain of market-based carbon policies: a global application to greenhouse gases from ruminant livestock production - B. Henderson; A. Golub; D. Pambudi; T. Hertel; C. Godde; M. Herrero; O. Cacho; P. Gerber (Mitigation and Adaptation Strategies for Global Change, 2018)

POP-contaminated sites from HCH production in Sabiñánigo, Spain - J. Fernández; M. A. Arjol; C. Cacho (Environmental Science and Pollution Research, 2013)

Influences of extratropical water masses on equatorial Pacific cold tongue variability during the past 160 ka as revealed by faunal evidence of planktic foraminifers - Pai‐Sen Yu; Markus Kienast; Min‐Te Chen; Isabel Cacho; Jos Abel Flores; Mahyar Mohtadi; Alan C. Mix (Journal of Quaternary Science, 2012)
Glacial cooling (∼1–5°C) in the eastern equatorial Pacific (EEP) cold tongue is often attributed to increased equatorial upwelling, stronger advection from the Peru–Chile Current (PCC), and to the more remote subpolar southeastern Pacific water mass. However, evidence is scarce for identifying unambiguously which process plays a more important role in driving the large glacial cooling in the EEP. To address this question, here we adopt a faunal calibration approach using planktic foraminifers with a new compilation of coretop data from the eastern Pacific, and present new downcore variation data of fauna assemblage and estimated sea surface temperatures (SSTs) for the past 160 ka (Marine Isotope Stage (MIS) 6) from ODP Site 1240 in the EEP. With significant improvement achieved by adding more coretop data from the eastern boundary current, our downcore calibration results indicate that most of the glacial cooling episodes over the past 160 ka in the EEP are attributable to increased influence from the subpolar water mass from high latitudes of the southern Pacific. By applying this new calibration of the fauna SST transfer function to a latitudinal transect of eastern Pacific (EP) cores, we find that the subpolar water mass has been a major dynamic contributor to EEP cold tongue cooling since MIS 6. Copyright © 2012 John Wiley & Sons, Ltd.

A retrospective study of climatic suitability for the tick Rhipicephalus (Boophilus) microplus in the Americas - A. Estrada‐Peña; C. Sánchez Acedo; J. Quílez; E. Del Cacho (Global Ecology and Biogeography, 2005)
Aim Climate change has the potential to have an impact on the distribution of ticks and tick‐borne diseases. This paper identifies the changes in climate suitability for the tick Rhipicephalus (Boophilus) microplus in the Americas by analysing climate data for the period 1950–99. Location The model was applied to the American continent. Methods A model based on Environmental Niche Modelling was used on a gridded (0.5°) long‐term (1950–99) climate data set. A map of the core range of the species was constructed, and areas where habitat suitability (HS) changes suddenly over short time periods were identified as regions of high sensitivity. Tendency of climate in the continent was evaluated and scenarios constructed for 2025 and 2050. Results Regions of high sensitivity included the southern USA, Mexico and western and central Argentina. Analysis of climate variables in these regions identified water vapour pressure deficit and evaporation as underlying the high sensitivity of habitat suitability in the USA and Mexico, and showed that episodes of high variability are linked to the El Niño Southern Oscillation. Projections of the tendency of HS as observed for the 1950–99 period point to an increase in this value in parts of the southern USA and in central Argentina, a finding that can be attributed to the progressive increase in minimum and yearly averaged temperatures. Conclusions Short‐term changes in climate may drive the system into unstable situations with sudden changes in habitat suitability for the target tick in specific zones of the Americas. Results suggest an increased abiotic (climate) suitability for R. microplus in areas whose habitat is currently unsuitable for this species.